PENGARUH KOMITMEN ORGANISASI DAN AMBIGUITAS PERAN TERHADAP KINERJA AUDITOR DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS: KANTOR AKUNTAN PUBLIK PEKANBARU, BATAM, DAN MEDAN) - Wulandari, Riezki; Satriawan, Raja Adri; Savitri, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aims to analyze and gets empirical prove at the effect of organizational commitment and role ambiguity on auditor performance with motivation as moderating variable. Respondens in this research is auditors who work in public accounting firm at Pekanbaru, Batam and Medan. The samples is selected by using purposive sampling, collection data method by using questionnaires with the number of sample of this research was 145 auditors from 29 public accounting firms. This research is a quantitative model with data analysis methods and regression analysis using multiple regression analysis and regression moderate. SPSS software version 17 to process data. The results of this research indicate that organizational commitment and role ambiguity have effect to auditor performance. Motivation is a moderating variable between influenced of organizational commitment and role ambiguity to auditor performance.Keywords: organization commitment, role ambiguity, motivation and auditor performance